Sistem Informasi Pemesanan Tiket Berbasis Web Mobile Pada Rental Mobil CV. Alda Jaya - Marwan M Londol; Hadis B Djapano (Akademi Manajemen Informatika dan Komputer Luwuk Banggai, 2022)
The purpose of this research is to build a mobile web-based ticket purchasing program for CV. ALDA JAYA, in order to make it easier for customers to purchase car tickets and prevent errors in recording purchase data for the rental itself. In the method that the authors take is the case study method. And the authors collect data through interviews, and document inspection. The results of this study are that the authors can create a mobile web-based application system or program that helps CV managers. Alda Jaya in purchasing and publishing information, as well as assisting the dissemination of information effectively and efficiently.